Analysis of Jokowi’s Commissive Speech Acts in 2014 and 2019 Inaugural Address: A Pragmatic Study - Salwa Fadila Firdaus; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Universitas Teknokrat Indonesia, 2020)
This article attempted to identify and describe the commissive acts in the inaugural addresses delivered by the Indonesian president Joko Widodo in 2014 and 2019. This includes the felicity condition of the addresses. The differences between commissive speech acts produced in his inauguration address and the second terms were also contrasted. The data were the transcripts of the addresses in both terms. Descriptive qualitative was implied in this study. The results found that there were two categories of commissive acts in the first term and four in the second term. In contrast with the first term which was only 11, in his second term he uttered 15 commissive acts. The results concluded that to maintain people’s trust in his second term, the speaker proposed more commissive acts than in the first term.